Heterogeneous impact of price spikes across countries and supply chain actors: An evidence from Central Asia and the Caucasus. A review - Ihtiyor Bobojonov; Ivan Duric; Thomas Glauben (Agricultural Economics (Zemědělská ekonomika), 2020)
The causes of food price spikes are complex, and their impact on different countries varies depending on production levels and the varied policies in place. Countries in Central Asia and the Caucasus (CAC) region have implemented a wide range of reforms that vary in form and speed. The existing scientific literature reports about the consequences of price spikes in CAC; however, to date, a comparison of impact between those countries has not been made in terms of the entire supply chain perspective. Therefore, this study investigates the impact of the price spikes on the entire wheat supply chain for the first time in CAC and discusses the role of policies. Another contribution of this study is an evidence-based analysis of the role of policy reformation in maintaining food security under price shocks. Our results indicate a very limited effect of price interventions and trade restrictions on dampening wheat prices in all countries. We find that only trade diversification policy had a positive effect on reducing the level of price spikes, and thus it might be a suitable policy measure for maintaining food security.
Keywords: 330; Caucasus; Central Asia; food security; price shocks; procurement policy; subsidies; wheat supply chains